Host-Induced Gene Silencing of the Aspergillus flavus O-Methyl Transferase Gene Enhanced Maize Aflatoxin Resistance - Olanike Omolehin; Yenjit Raruang; Dongfang Hu; Zhu-Qiang Han; Surassawadee Promyou; Robert L. Brown; Qijian Wei; Kanniah Rajasekaran; Jeffrey W. Cary; Kan Wang; Dan Jeffers; Zhi-Yuan Chen (Toxins)
Maize is one of the major crops that are susceptible to Aspergillus flavus infection and subsequent aflatoxin contamination, which poses a serious health threat to humans and domestic animals. Here, an RNA interference (RNAi) approach called Host-Induced Gene Silencing (HIGS) was employed to suppress the O-methyl transferase gene (omtA, also called aflP), a key gene involved in aflatoxin biosynthesis. An RNAi vector carrying part of the omtA gene was introduced into the B104 maize line. Among the six transformation events that were positive for containing the omtA transgene, OmtA-6 and OmtA-10 were self-pollinated from T1 to T4, and OmtA-7 and OmtA-12 to the T6 generation. These four lines showed at least an 81.3% reduction in aflatoxin accumulation at the T3 generation under laboratory conditions. When screened under field conditions with artificial inoculation, OmtA-7 at T5 and T6 generations and OmtA-10 at T4 generation showed a reduction in aflatoxin contamination between 60% and 91% (p < 0.02 to p < 0.002). In order to develop commercial maize lines with enhanced aflatoxin resistance, the omtA transgene in OmtA-7 was introduced into three elite inbred lines through crossing, and the resulting crosses also exhibited significantly lower aflatoxin accumulation compared to crosses with non-transgenic controls (p < 0.04). In addition, high levels of omtA-specific small RNAs were only detected in the transgenic kernel and leaf tissues. These results demonstrate that suppression of omtA through HIGS can enhance maize resistance to aflatoxin contamination, and this resistance can be transferred to elite backgrounds, providing a viable and practical approach to reduce aflatoxin contamination in maize.